Identification of Potential circRNA-microRNA-mRNA Regulatory Network in Skeletal Muscle - Das, Arundhati; Shyamal, Sharmishtha; Sinha, Tanvi; Mishra, Smruti Sambhav; Panda, Amaresh C. (Frontiers in Molecular Biosciences, 2021)
Circular RNAs (circRNAs) are a newly discovered family of regulatory RNAs generated through backsplicing. Genome-wide profiling of circRNAs found that circRNAs are ubiquitously expressed and regulate gene expression by acting as a sponge for RNA-binding proteins (RBPs) and microRNAs (miRNAs). To identify circRNAs expressed in mouse skeletal muscle, we performed high-throughput RNA-sequencing of circRNA-enriched gastrocnemius muscle RNA samples, which identified more than 1200 circRNAs. In addition, we have identified more than 14,000 and 15,000 circRNAs in aging human skeletal muscle tissue and satellite cells, respectively. A subset of abundant circRNAs was analyzed by RT-PCR, Sanger sequencing, and RNase R digestion assays to validate their expression in mouse skeletal muscle tissues. Analysis of the circRNA-miRNA-mRNA regulatory network revealed that conserved circNfix might associate with miR-204-5p, a suppressor of myocyte enhancer factor 2c (Mef2c) expression. To support the hypothesis that circNfix might regulate myogenesis by controlling Mef2c expression, silencing circNfix moderately reduced Mef2c mRNA expression and inhibited C2C12 differentiation. We propose that circNfix promotes MEF2C expression during muscle cell differentiation in part by acting as a sponge for miR-204.